Comparative efficacy and safety of intravenous ferric carboxymaltose and iron sucrose for iron deficiency anemia in obstetric and gynecologic patients: A systematic review and meta-analysis. Issue 20 (21st May 2021) - Shin, Hye Won; Go, Doo Yeon; Lee, Suk Woo; Choi, Yoon Ji; Ko, Eun Ji; You, Hae Sun; Jang, Yoo Kyung
Abstract: Introduction: Iron deficiency anemia (IDA) is common among obstetric and gynecologic patients. This systematic review aimed to assess the comparative efficacy and safety of commonly used intravenous (IV) iron formulations, ferric carboxymaltose (FCM), and iron sucrose (IS) in the treatment of IDA in obstetric and gynecologic patients. Methods: We systematically searched PubMed, EMBASE, Cochrane CENTRAL, and Google Scholar for eligible randomized controlled trials (RCTs) comparing IV iron replacement using FCM and IS up to October 2019. The primary outcome was to compare the efficacy of FCM and IS, assessed by measuring serum hemoglobin (Hb) and ferritin levels before and after iron replacement. The secondary outcome was to compare the safety of FCM and IS, assessed by the incidence of adverse events during iron replacement. The meta-analysis was performed using RevMan 5.3. Results: We identified 9 RCTs with 910 patients (FCM group, n = 456; IS group, n = 454). Before iron replacement, FCM and IS group patients had similar baseline Hb (mean difference [MD], 0.04 g/dL; 95% confidence interval [CI], −0.07 to 015; I 2 = 0%; P = 0.48) and ferritin levels (MD, −0.42 ng/mL; 95% CI, −1.61 to 0.78; I 2 = 45%; P = 0.49). Following iron replacement, patients who received FCM had higher Hb (MD, 0.67; 95% CI, 0.25–1.08; I 2 = 92%; P = 0.002) and ferritin levels (MD, 24.41; 95% CI, 12.06–36.76; I 2 = 75%; P = 0.0001) than patients who received IS. FCM group showed a lower incidence of adverse events following iron replacement than IS group (risk ratio, 0.53; 95% CI, 0.35–0.80; I 2 = 0%; P = 0.003). Serious adverse events were not reported in any group. Conclusion: FCM group showed better efficacy in increasing Hb and ferritin levels and a favorable safety profile with fewer adverse events compared with IS group for IDA treatment among obstetric and gynecologic patients. However, this meta-analysis was limited by the small number of RCTs and high heterogeneity. Trial registration: The review was prospectively registered with the International Prospective Registry of Systematic Reviews (https://www.crd.york.ac.uk/prospero/, registration number CRD42019148905). Abstract : Supplemental Digital Content is available in the text